Controlled synthesis of ZnO from nanospheres to micro-rods and its gas sensing studies - Navale, Shalaka C.; Gosavi, S. W.; Mulla, Imtiaz S. (Talanta, 2008)
1D ZnO rods are synthesized using less explored hydrazine method. Here we find, besides being combustible hydrazine can also be used as a structure-directing agent. The ratio of zinc nitrate (ZN) to hydrazine is found to control the morphology of ZnO. At lower concentration of ZN as compared with hydrazine the morphology of ZnO is found to be spherical. As we increase the hydrazine content the morphology changes from spherical (diameter similar to 100 nm) to the elongated structures including shapes like Y, T as well dumbbell (diameter similar to 40 nm and length similar to 150 nm). Interestingly for more than 50% of hydrazine ZnO micro-rods are formed. Such rods are of diameter similar to 120 mn having length of about 1 mu m for ZN to hydrazine ratio of 1:9, isolated as well as bundle of rods are seen in scanning electron microscopy (SEM). The X-ray diffraction (XRD) reveals the phase formation with average particle size of 37 nm as calculated using Scherrer's formula. The high-resolution transmission electron microscopy (HRTEM) is also done to confirm the d-spacing in ZnO. Gas sensing study for these samples shows high efficiency and selectivity towards LPG at all operating temperatures. Photoluminescence (PL) study for these samples is performed at room temperature to find potential application as photoelectric material. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Hydrazine; LPG sensor; Nanostructures; photoluminescence; ZnO

EPR and DRS evidence for NO2 sensing in Al-doped ZnO - Navale, Shalaka C.; Ravi, V.; Srinivas, D.; Mulla, Imtiaz S.; Gosavi, S. W.; Kulkarni, S. K. (Sensors and Actuators B-Chemical, 2008)
Zinc oxide (ZnO) is a well-known semiconducting multifunctional material wherein properties right from the morphology to gas sensitivity can be tailor-made by doping or surface modification. Aluminum (Al)-incorporated porous zinc oxide (AI:ZnO) exhibits good response towards NO2 at low-operating temperature. The NO2 gas concentration as low as 20 ppm exhibits S = 17% for 5 wt. % Al-incorporated ZnO. The NO2 response increases with operating temperature and concentration and reaches to its maximum at 300 degrees C without any interference from other gases such as SO3, HCl, LPG and alcohol. Physico-chemical characterization likes differential thermogravimetric analysis (TG-DTA) electron paramagnetic resonance (EPR) and diffused reflectance spectroscopy (DRS) have been used to understand the sensing behavior for pure and A]-incorporated ZnO. The TG-DTA depicts formation of ZnO phase at 287 degrees C. The EPR study reveals distinct variation for O- (g=2.003) and Zn interstitial (g = 1.98) defect sites in pure and Al:ZnO. The DRS studies elucidate signature of adsorbed NO, species in aluminium-incorporated zinc oxide indicating its tendency to adsorb these species even at low temperatures. This paper is an attempt to correlate the gas sensing behavior with the physico-chemical studies such as EPR and DRS. (c) 2007 Published by Elsevier B.V.
Keywords: aluminum doping; DRS; EPR; NO2 sensor; ZnO

Field emission properties of Al-doped ZnO nanostructures - Navale, Shalaka C.; Sheini, Farid Jamali; Patil, Sandip S.; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A.; Gosavi, Suresh W. (Journal of Nano Research, 2009)
Field emission from Al-doped ZnO nanostrcutures has been investigated in planar diode configuration under ultra high vacuum conditions. The Al-doped ZnO nanostructures were synthesized by co-precipitation method with varying aluminium concentrations. The as- synthesized product was characterized by x-ray diffraction, scanning electron microscope and energy dispersive x-ray analysis. The threshold field required to draw a current density of similar to 1 mu A/cm(2) was observed to be similar to 2.0 V/mu m and similar to 2.3 V/mu m for Al-doped ZnO nanostructures synthesized with aluminium concentrations of 1% and 3%, respectively. The Fowler- Nordheim (F-N) plots for both the specimens exhibit non-linear behaviour, which is observed to be specimen dependent. The nonlinearity observed in the F-N plots has been interpreted on the basis of the theory of electron emission from semiconductor emitters. The field enhancement factors, estimated from the slope of the F-N plots, are found to be similar to 9.3 x 10(3) and 3.9 x 10(3) for 1% and 3% Al-doped ZnO emitters, respectively. The high values of the field enhancement factor Suggest that the emission is from the nanostructures. The emission current stability measured at the preset value of similar to 2 mu A over a period of more than three hours is found to be fairly stable. The results indicate use of Al-doped ZnO nanostructures as promising emitters for field emission based devices.
Keywords: field emission; Fowler-Nordheim plots; Nanostructures; ZnO

Investigations on Ru doped ZnO: strain calculations and gas sensing study - Navale, Shalaka C.; Ravi, V.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2009)
Pure and ruthenium (Ru) doped nano-crystalline zinc oxide (ZnO) powders were synthesized by using well-known citrate gel route. Citric acid acts as a chelating agent and thus helps in the formation of nanoparticles. The detailed X-ray diffraction (XRD) studies using Hall equation reveal that in the nanoscale dimensions, incorporation of Ru modulates the lattice strain. It is interesting to note that on Ru doping, the compressive strain present in the undoped ZnO changes into tensile strain. We have tested the response of these specimens individually for reducing gases like H(2), LPG (liquefied petroleum gas), C(2)H(5)OH (ethanol), CO, acetone and oxidizing gases like NO, and Cl(2). Undoped ZnO responses perceptibly to LPG while Ru doped sample highly senses ethanol vapors. This might be due to either change in composition on Ru doping or/and difference between basicity of LPG and C(2)H(5)OH vapors. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Citrate gel; Ethanol sensor; LPG sensor; Nanomaterials; ruthenium

Photoluminescence and gas sensing study of nanostructured pure and Sn doped ZnO - Navale, Shalaka C.; Mulla, Imtiaz S. (Materials Science & Engineering C-Biomimetic and Supramolecular Systems, 2009)
The nanostructured pure and Sn doped ZnO have been synthesized by the thermal evaporation technique. The influence of Sri oil the morphology and structure is investigated by using scanning electron microscopy (SEM), X-ray diffraction (XRD) and energy dispersive X-ray (EDX) analysis techniques, The SEM images indicate change in the growth pattern from nanowires of pure ZnO to tetrapods for Sn doped ZnO. Pure ZnO nanowires exhibit selective response towards acetone vapors while on Sri doping the response decreases. The non-stiochiometry and the morphology of ZnO arc probably responsible for such a difference in gas response. However increase in temperature doesn't improve the sensing behavior. The photoluminescence (PL) Studies reveal UV emission in pure ZnO which shifts to green emission oil doping of Sri. All rights reserved. (C) 2008 Elsevier B V. All rights reserved.
Keywords: Acetone; Gas sensors; Sn doped ZnO

Nanowires of silver-polyaniline nanocomposite synthesized via in situ polymerization and its novel functionality as an antibacterial agent - Tamboli, Mohaseen S.; Kulkarni, Milind V.; Patil, Rajendra H.; Gade, Wasudeo N.; Navale, Shalaka C.; Kale, Bharat B. (Colloids and Surfaces B-Biointerfaces, 2012)
Silver-polyaniline (Ag-PANI) nanocomposite was synthesized by in situ polymerization method using ammonium persulfate CAPS) as an oxidizing agent in the presence of dodecylbenzene sulfonic acid (DBSA) and silver nitrate (AgNO3). The as synthesized Ag-PANI nanocomposite was characterized by using different analytical techniques such as UV-visible (UV-vis) and Fourier transform Infrared spectroscopy (FT-IR), field emission scanning electron microscopy (FE-SEM), thermo gravimetric analysis (TGA). X-ray diffraction (XRD), and transmission electron microscopy (TEM). UV-visible spectra of the synthesized nanocomposite showed a sharp peak at similar to 420 nm corresponding to the surface plasmon resonance (SPR) of the silver nanoparticles (AgNPs) embedded in the polymer matrix which is overlapped by the polaronic peak of polyaniline appearing at that wavelength. Nanowires of Ag-PANI nanocomposite with diameter 50-70 nm were observed in FE-SEM and TEM. TGA has indicated an enhanced thermal stability of nanocomposite as compared to that of pure polymer. The Ag-PANI nanocomposite has shown an antibacterial activity against model organisms, a gram positive Bacillus subtilis NCIM 6633 in Mueller-Hinton (MH) medium, which is hitherto unattempted. The Ag-PANI nanocomposite with monodispersed AgNPs is considered to have potential applications in sensors, catalysis, batteries and electronic devices. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: antibacterial activity; Conducting poly(aniline); In situ polymerization; Nanocomposite

Response to the comments on `Investigations on Ru doped ZnO: strain calculations and gas sensing study' - Navale, Shalaka C.; Ravi, V.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2013)